Re-Design Alat Pencelupan Kain Batik untuk Mengurangi Resiko Musculoskeletal Disorders (MSDs) Menggunakan Metode Ergonomi - Nurfajriah .; Rifa Arifati (JURNAL CITRA WIDYA EDUKASI, 2017)
Ergonomics is a combination of several other sciences that include human systems, machines and environments that interact (International Ergonomic Association), in addition to ergonomics also learn about design of work tools and work environment in accordance with the capacity and limitations of humans. Ergonomics is aimed at achieving conformity between man and his job in order to achieve prosperity. This anthropometry study can be conducted on a wide range of jobs, both in large industries and small industries. One of them is batik industry. Batik industry is currently an industry that is experiencing rapid development. Batik Bogor has typical motifs such as drizzling rain, lotus, deer head, and cleaver. From the analysis that has been done is known that the condition of work posture on the dyeing of batik cloth is very risky cause musculoskeletal disorders injuries. The purpose of this research is to redesign the work equipment. Based on the Nordic Body Map questionnaire given to workers, it is known to average the biggest pain complaints on the neck, back and waist. The incidence of such risks and complaints is due to unnatural operator posture, and lasts for a long time. So given the proposed redesign of dyeing equipment to support operator comfort in work. Proposed designs have been adapted to anthropometric dimensions and in accordance with operator requirements so as to overcome complaints and musculoskeletal injuries.